Habitat use of the Wood Warbler Phylloscopus sibilatrix during spring migration versus breeding season based on citizen science data. Issue 3 (3rd July 2017) - Weisshaupt, Nadja; Rodríguez-Pérez, Javier
ABSTRACT: Capsule: Citizen science data on Wood Warblers Phylloscopus sibilatrix showed that the species non-selectively used a wide variety of habitats during migration but had a tendency for settling to breed in forest and natural areas. Aims: We tested the hypothesis that habitat used during spring stopovers in Spain differed from habitat use during the breeding period in Switzerland in a year of exceptional abundance as a result of persistent easterly winds in the Mediterranean. Methods: Habitat use during spring migration 2015 was compared by using bootstrapping resampling techniques on citizen science data from Spain and Switzerland, comparing the land-cover categories between locations of observations with random pseudo-absences. Results: Wood Warblers showed no preference for habitat features during migration and covered practically all available habitat types from urbanized areas to wetlands and forests, whereas in the breeding range birds showed an increasing tendency to be present in forest habitats. Conclusions: Habitat use during spring migration covered most available habitat types from urbanized areas to wetlands and forests. Breeding habitat use was restricted to forested areas. Citizen science allowed a quick collection of biological data over a wide area to potentially identify large-scale biological patterns. This is essential to potentially manage international conservation efforts for declining species.